Reliability of the Multiplex CytoBead CeliAK Immunoassay to Assess Anti-tTG IgA for Celiac Disease Screening - Abdukhakimova, Diyora; Dossybayeva, Kuanysh; Grechka, Anna; Almukhamedova, Zhaina; Boltanova, Alyona; Kozina, Larissa; Nurgaliyeva, Kadisha; Hasanova, Liliya; Tanko, Matthew N.; Poddighe, Dimitri (Frontiers in Medicine, 2021)
Background and Objective: The diagnosis of Celiac Disease (CD) is first based on the positivity for specific serological markers. The CytoBead CeliAK immunoassay simultaneously measures antibodies (IgA) directed to tissue transglutaminase (tTG), endomysium (EMA), and deamidated gliadin (DG), in addition to providing a control for total IgA levels. The aim of this study is to assess the reliability of this multiplex assay to detect anti-tTG IgA positive patients, compared with a conventional single-parameter enzyme-linked immunosorbent assay (ELISA). Methods: Serum samples from 149 pediatric patients were assessed by both CytoBead CeliAK immunoassay and ELISA, in order to evaluate their concordance for the measurement of anti-tTG IgA. Results: The measurement of anti-tTG IgA by CytoBead CeliAK immunoassay basically showed a complete concordance rate with the conventional and single-parameter ELISA, according to the respective cutoff values (3 U/ml and 10 U/ml). Conclusions: Our comparative analysis demonstrates a substantial equivalency between multiplex CytoBead CeliAK assay and the single-parameter conventional ELISA to assess anti-tTG IgA antibody in the context of the screening for CD in children. Importantly, CytoBead CeliAK assay could present some preanalytic, analytic, and economic advantages.